2017
DOI: 10.1177/2325967117718781
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Menstrual Cycle and Contraceptives on ACL Injuries and Laxity: A Systematic Review and Meta-analysis

Abstract: Background:Women are at substantially greater risk for anterior cruciate ligament (ACL) injuries than are men.Purpose:To conduct a systematic review and meta-analysis of the literature to clarify the effect of the menstrual cycle and contraceptives on the laxity of and noncontact injuries to the ACL.Study Design:Systematic review; Level of evidence, 4.Methods:Searches were conducted using MEDLINE (1946–August 2016), the Cochrane Library Database, clinical trial registries, and related reference lists. Search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 55 publications
(108 reference statements)
1
127
2
4
Order By: Relevance
“…Accordingly, we had expected an effect of oestrogenic hormones on the joints in girls, which, however, did not occur. Because of the known effect of oral contraceptives on the general mobility, it was at least plausible to exclude subjects taking that medication from the analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we had expected an effect of oestrogenic hormones on the joints in girls, which, however, did not occur. Because of the known effect of oral contraceptives on the general mobility, it was at least plausible to exclude subjects taking that medication from the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption is debatable, because even if the knee mobility changes during the menstrual cycle, hormone differences could not be measured . However, it has been frequently verified that the oral contraceptives (female sex hormone) heighten the joint mobility . At the same time, the male sex hormone testosterone reduces the overall joint mobility, as shown in animal tests—a fact that might explain the lower prevalence of hypermobility in males.…”
Section: Introductionmentioning
confidence: 99%
“…It is described that a decrease in fibroblast proliferation and collagen synthesis was seen with increasing estradiol concentration and this effect was attenuated with increasing progesterone concentration [3]. Previous studies have demonstrated the luteal phase to have the highest rate of ACL injuries [4] yet the progesterone level peaks in this phase. Would this not result in increased fibroblast proliferation and collagen synthesis hence contradicting the proposed mechanism?…”
Section: Ellis Muggleton and Tülin Muggletonmentioning
confidence: 99%
“…This is why numerous studies have tried to link a specific phase of the menstrual cycle associated with specific levels of estrogen and progesterone to the ACL injury risk . However, results from studies differ widely, and even reviews vary in their conclusions . While one review stated that definite conclusions are not warranted regarding the association between menstrual cycle and ACL injury risk, another review identified a predisposition to injury in the pre‐ovulatory phase and yet another one suggested that the injury risk was increased during the ovulatory phase …”
Section: Introductionmentioning
confidence: 99%